The role of stretch, tachycardia and sodium‐calcium exchanger in induction of early cardiac remodelling. Issue 15 (22nd June 2020) - Djalinac, Natasa; Ljubojevic‐Holzer, Senka; Matzer, Ingrid; Kolesnik, Ewald; Jandl, Katharina; Lohberger, Birgit; Rainer, Peter; Heinemann, Akos; Sedej, Simon; von Lewinski, Dirk; Bisping, Egbert
Abstract: Stretch and tachycardia are common triggers for cardiac remodelling in various conditions, but a comparative characterization of their role in the excitation‐transcription coupling (ETC) and early regulation of gene expression and structural changes is lacking. Here, we show that stretch and tachycardia directly induced hypertrophy of neonatal rat cardiac myocytes and also of non‐myocytes. Both triggers induced similar patterns of hypertrophy but had largely distinct gene expression profiles. ACTA1 served as good hypertrophy marker upon stretch, while RCAN1 was found increased in response to tachycardia in a rate‐dependent fashion. Mechanistically, several calcium‐handling proteins, including the sodium‐calcium exchanger (NCX), contributed to ETC. Phosphorylation of the calcium/calmodulin‐dependent protein kinase II (CaMKII) was elevated and occurred downstream of NCX activation upon tachycardia, but not stretch. Microarray profiling revealed that stretch and tachycardia regulated around 33% and 20% genes in a NCX‐dependent manner, respectively. In conclusion, our data show that hypertrophy induction by stretch and tachycardia is associated with different gene expression profiles with a significant contribution of the NCX.